2013
DOI: 10.1080/09593330.2012.744431
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-enhanced UV/H2O2degradation of an azo dye (tartrazine): optimization, colour removal, mineralization and ecotoxicity

Abstract: This study optimizes two factors, pH and initial [H2O2], in the ultraviolet (UV)/H2O2/microwave (MW) process through experimental design and assesses the effect of MWs on the colour removal of an azo-dye (tartrazine) solution that was favoured by an acidic pH. The estimated optimal conditions were: initial [H2O2] = 2.0 mmol L(-1) and pH = 2.6, at 30 +/- 2 degrees C. We obtained colour removals of approximately 92% in 24 min of irradiation (EDL, 244.2 W), following zero order kinetics: k = (3.9 +/- 0.52) x 10(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 33 publications
0
8
0
3
Order By: Relevance
“…The UV-H 2 O 2 process is one of the oldest AOPs and can treat various organic pollutants based on the generation of OH·. Some of its advantages have attracted the attention of researchers, for example, the commercial availability of the oxidant, the formation of two OH· from each H 2 O 2 molecule under photocatalysis, minimal capital investment, cost-effectiveness, and simple operating procedures [126].…”
Section: Mw-photochemical Processmentioning
confidence: 99%
“…The UV-H 2 O 2 process is one of the oldest AOPs and can treat various organic pollutants based on the generation of OH·. Some of its advantages have attracted the attention of researchers, for example, the commercial availability of the oxidant, the formation of two OH· from each H 2 O 2 molecule under photocatalysis, minimal capital investment, cost-effectiveness, and simple operating procedures [126].…”
Section: Mw-photochemical Processmentioning
confidence: 99%
“…AOPs involve the generation of hydroxyl radicals and complete oxidization of such pollutants including dyes converted into end products, such as CO 2 , H 2 O, etc [7]. Recent literature has indicated that hybridization of different AOPs has been found to be more efficient for the wastewater treatment than individual oxidation process [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…One such example is the microwave assisted degradation of Acid orange 7 dye in 10 min, carried out on polyaniline substrate used as catalyst [12]. Microwave energy has also been utilized for degrading dyes in different combinations such as with UV radiation and O 3 [13], and sometimes with UV and H 2 O 2 [14,15]. It has also been reported that decreasing the starting reaction temperature to sub-zero levels can change the products in microwave assisted organic reactions [16].…”
Section: Introductionmentioning
confidence: 99%